2011
DOI: 10.1007/s00468-011-0634-y
|View full text |Cite
|
Sign up to set email alerts
|

Environment and position of first bud to break on apple shoots affects lateral outgrowth

Abstract: A study was conducted to determine which bud (terminal or lateral) breaks first, and thereby exerts primigenic dominance, on 'Granny Smith' and 'Golden Delicious', 1-year-old apple (Malus 9 domestica Borkh.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
(68 reference statements)
1
13
0
2
Order By: Relevance
“…Lauri (2007) states that the influence of apical dominance is coordinated by basipetal transport of auxin, which exerts direct inhibition on the growth of axillary buds. For Maguylo et al (2012), the growth of lateral buds is controlled mainly by paradormancy, rather than by the intrinsic state of endodormancy. Given this effect of apical buds on lateral buds, and the observation that lateral budburst was low for all treatments, the significant differences eventually observed between thermal regimes become unimportant (Figures 2 B and 2 D).…”
Section: Resultsmentioning
confidence: 99%
“…Lauri (2007) states that the influence of apical dominance is coordinated by basipetal transport of auxin, which exerts direct inhibition on the growth of axillary buds. For Maguylo et al (2012), the growth of lateral buds is controlled mainly by paradormancy, rather than by the intrinsic state of endodormancy. Given this effect of apical buds on lateral buds, and the observation that lateral budburst was low for all treatments, the significant differences eventually observed between thermal regimes become unimportant (Figures 2 B and 2 D).…”
Section: Resultsmentioning
confidence: 99%
“…However, our results strongly suggested that the growing potential of the bud depends both on an endogenous growing ability Table 1 Hydraulic conductance (K stem-bud ; mmol MPa -1 s -1 ), water potential (WP; MPa) and relative water content (RWC; %) before budburst (mid-March 2012), and proleptic lateral growth (PLG; %) on one-year-old wood (July 2012) in the distal third of parent shoots of four apple cultivars grown under contrasted winter temperature treatments, cold winter and mild winter, with 1,428 and 99 h below 7.2°C, respectively (Lauri and Térouanne 1998) in relation to the number of appendages in the bud positively related to K stem-bud (Lauri et al 2008) and on a whole-shoot effect. This latter effect is likely related to highly dynamic competitions among buds before budburst through a temporal (e.g., the first bud to burst has a higher growth potential, also called primigenic dominance) and/or a positional effect along the stem (Maguylo et al 2012), and between buds and the parent shoot (Champagnat 1983). However, interactions between the bud endogenous potential and the parent stem are still not fully understood, and large buds with functional vascular connections may be fully dormant (Brewer et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Individual bud traits were considered for buds in the distal third of all one-year-old shoots, in the two temperature treatments, usually characterized by the highest budburst frequency under the cold winter conditions (Maguylo et al 2012). Destructive bud sampling was done at three consecutive times in the dormancy period during the 2011-2012 Winter: beginning of January 2012, i.e., at the end of the supposed endodormancy (Mauget and Rageau 1988), mid-February and mid-March.…”
Section: Plant Materials and Experimental Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…O material experimental para avaliar a evolução da dormência nos métodos biológicos utilizados consistiu de ramos de ano ou do ciclo anterior (brindilas) das cultivares Royal Gala e Castel Gala, que representam, respectivamente, genótipos de média e baixa exigência de frio hibernal (DENARDI; SECCON, 2005;PALLADINI;POLA, 2006). As brindilas foram amostradas com 20 a 25 cm de comprimento, apresentando em média oito gemas, em pomar comercial localizado no município de Papanduva -SC (26°26′68″S, 50°05′47″W e 788 m de altitude).…”
Section: Methodsunclassified